2021
DOI: 10.1111/jcpp.13460
|View full text |Cite
|
Sign up to set email alerts
|

The early course and treatment of posttraumatic stress disorder in very young children: diagnostic prevalence and predictors in hospital‐attending children and a randomized controlled proof‐of‐concept trial of trauma‐focused cognitive therapy, for 3‐ to 8‐year‐olds

Abstract: Background: The introduction of developmentally adapted criteria for posttraumatic stress disorder (PTSD) has improved the identification of ≤6-year-old children with clinical needs. Across two studies, we assess predictors of the development of PTSD in young children (PTSD-YC), including the adult-led acute stress disorder (ASD) diagnosis, and provide proof of principle for cognitive-focused therapy for this age range, with the aim of increasing treatment options for children diagnosed with PTSD-YC. Method: S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Addressing post-traumatic cognitions is fundamental in helping children recover from the impact of traumatic experiences, and TF-CBT intends to identify maladaptive cognitions and help children develop more adaptive thought patterns and coping mechanisms [10,[48][49][50][51][52][53]. Several clinical trials suggested that post-traumatic cognitions are important treatment targets [1,54,55]. However, it is not clear whether app-assisted TF-CBT-based intervention could substantially improve the cognitions of children hospitalized in psychiatry units.…”
Section: Post-traumatic Cognitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Addressing post-traumatic cognitions is fundamental in helping children recover from the impact of traumatic experiences, and TF-CBT intends to identify maladaptive cognitions and help children develop more adaptive thought patterns and coping mechanisms [10,[48][49][50][51][52][53]. Several clinical trials suggested that post-traumatic cognitions are important treatment targets [1,54,55]. However, it is not clear whether app-assisted TF-CBT-based intervention could substantially improve the cognitions of children hospitalized in psychiatry units.…”
Section: Post-traumatic Cognitionsmentioning
confidence: 99%
“…Traumatic experiences like abuse, natural disasters, or loss of loved ones, may result in numerous harmful consequences on mental health [1][2][3][4], 2.6 times increasing the risk of depressive disorders [5], not to mention post-traumatic stress disorder (PTSD) [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, the studies identified were not comparable enough to recommend a particular treatment. In a recent development, Hitchcock et al [28] utilised CBT-3M, an adapted version of TF-CBT for adolescents and older children, in a pilot study of children aged 3–8 years. CBT-3M ( n = 18) was compared to a waitlist control ( n = 19).…”
Section: Special Populationsmentioning
confidence: 99%
“…Follow-up studies have indicated profit sustainability for 6 months, 1 year, and 2 years after treatment. Therefore, TF-CBT is "supported and efficacious in PTSD, depressive and anxiety symptoms, conduct problems, sexualized behaviors, and shame, negative cognitions evoked by trauma, interpersonal trust, and social competence" [11,12,40,[51][52][53][54][57][58][59].…”
Section: Tf-cbtmentioning
confidence: 99%
“…To be more specific, TF-CBT was applied to English-speaking and Hispanic populations after the terrorist attacks of September 11, 2001, and was effective in reducing PTSD symptoms [55,60]. An adapted model in two studies has also revealed significant improvement in both PTSD and grief symptoms [5,53]. Moreover, parents have also reported a significant reduction in their distress and depressive symptomatology and significant gains in their ability to support and deal with their children's behavioral difficulties [61].…”
Section: Tf-cbtmentioning
confidence: 99%